2021
DOI: 10.3168/jdsc.2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of polyhexamethylene biguanide nanoparticles against mastitis-causing Staphylococcus aureus

Abstract: Polyhexamethylene biguanide (PHMB) nanoparticles (NP) developed for this study presented antimicrobial activity against mastitis-causing Staphylococcus aureus at lower concentrations than PHMB alone, chlorhexidine digluconate, povidone-iodine, and sodium dichloroisocyanurate. Thus, PHMB NP present potential for the development of new dipping solutions. Highlights• The PHMB NP were developed by layer-by-layer assembly.• Mastitis-causing Staph. aureus were inhibited by PHMB NP at low concentrations relative to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…One research reported that low PHMB concentrations (4 mg/L) killed almost 100% intracellular S. aureus (EMRSA-15 and USA300), and that PHMB entered the keratinocytes, localized with EMRSA-15 and remained continuously over 5 h [30]. One study reported MIC 90 values of PHMB ≥ 0.5 µg/mL against mastitiscausing S. aureus [31]. Another study evaluated the antimicrobial activity of PHMB against mastitis-causing Prototheca spp., and the MIC 90 values of PHMB was 2 µg/mL, which was lower than sodium dichloroisocyanurate (1400 µg/mL) and sodium hypochlorite (2800 µg/mL) against P. bovis isolates [32].…”
Section: Discussionmentioning
confidence: 99%
“…One research reported that low PHMB concentrations (4 mg/L) killed almost 100% intracellular S. aureus (EMRSA-15 and USA300), and that PHMB entered the keratinocytes, localized with EMRSA-15 and remained continuously over 5 h [30]. One study reported MIC 90 values of PHMB ≥ 0.5 µg/mL against mastitiscausing S. aureus [31]. Another study evaluated the antimicrobial activity of PHMB against mastitis-causing Prototheca spp., and the MIC 90 values of PHMB was 2 µg/mL, which was lower than sodium dichloroisocyanurate (1400 µg/mL) and sodium hypochlorite (2800 µg/mL) against P. bovis isolates [32].…”
Section: Discussionmentioning
confidence: 99%
“…PHMB can also be encapsulated into chitosan and alginate by the layer-bylayer self-assembly method. 146 Furthermore, it was reported that PHMB could be immobilized into γ-cyclodextrin (CD) to form inclusion complexes. 147,148 The prepared γ-CD-PHMBcomplexes exhibited a significant antifungal effect against C. albicans and M. pachydermatis.…”
Section: Phmb-based Drug Delivery Systemmentioning
confidence: 99%
“…The MIC90 of S. aureus was determined using a microdilution assay. PHMB NP had the lowest MIC value (0.03 g/mL) to inhibit 90% of S. aureus followed by chlorhexidine digluconate (0.25 g/mL) and PHMB (0.5 g/mL) [27]. Anti-biofilm activities were investigated in another investigation by treating S. aureus biofilms and assessing the impact on biofilm mass in vitro.…”
Section: Synthetic Antimicrobial Cationic Polymersmentioning
confidence: 99%
“…PHMB-coupled nanoparticles have an impressive MIC90 of 0.03 g/mL while PHMB alone has a value of 0.5 g/mL in controlling S. aureus infection. Effective Anti-biofilm activity requires a concentration of 15 mg/L [27,28] Polymeric Quaternary Ammonium Compounds (QACs) By quaternary ammonium group modification of polyethyleneimine (PEI) nanoparticles, efficient and longlasting antibacterial effects can be achieved especially in the case of oral bacteria [29,30]…”
Section: Polyamidoamine (Pamam) Dendrimersmentioning
confidence: 99%